Poster 202: Patellar Stabilization Procedures Not Performed to Address Alta Decrease Patellar Height. Issue 7 (30th July 2022) - Anderson, Gregory; Hart, Joseph; Shank, Kaitlyn; Yalçin, Sercan; Fury, Matthew; Elias, John; Tanaka, Miho; Farrow, Lutul; Diduch, David; Cosgarea, Andrew; Kreulen, Timothy
Objectives: The objective of this study is to understand the effect that operative patellar stabilization (without concomitant distalization) has on patellar height. Specifically, we studied MPFL reconstruction (MPFLr), non-distalizing tibial tubercle osteotomy (TTO), and trochleoplasty. There are several established risk factors for patellar instability, including patella alta and trochlear dysplasia. Traditionally, in patients with patellar instability with associated significant patella alta, the elevated patellar height can be corrected with distalizing TTO or patellar tendon shortening. Shortening the patellar tendon or moving the tubercle inferiorly corrects the alta and, in turn, causes the patella to engage the trochlea earlier in flexion providing increased bony restraint. Patients with trochlear dysplasia can be treated with trochleoplasty, where the abnormally contoured trochlea is corrected. MPFL reconstruction (MPFLr) is often performed in the absence of predisposing anatomic abnormality or in addition to either of the aforementioned procedures. The reconstruction restores the medial restraint to the patella. Recent literature suggests that MPFLr without distalizing TTO decreases patellar height. Luceri et al showed a decrease in patellar height at a mean follow up of 18.4 ± 12.0 months in a population with an average age of 25.0 using a technique with two patellar tunnels and tensioning the knee in 30 degrees of flexion. Lykissas showed similar results in an adolescent population (mean age 14.2) with a mean follow up of 6 months using a technique with a single patellar limb and tensioning their grafts in 45 degrees of knee flexion. Fabricant also found a decrease in patellar height in adolescents (mean age 14.9) at 3 months of follow up. Their technique featured 2 tunnels in the patella with the graft tensioned in 20 degrees of knee flexion. Roessler, however, did not observe a change in patellar height in a series of 32 patients with an average age of 29.7. We studied the effect of patellar instability surgery on patellar height to better elucidate why there are conflicts in the literature. While the current literature focuses on MPFLr, we also studied non-distalizing TTO and trochleoplasty. We hypothesized that patellar stabilization procedures that were not performed to address patella alta decrease patellar height. Methods: A multi-center, retrospective chart review was conducted at Johns Hopkins, University of Virginia, Cleveland Clinic, and Massachusetts General Hospital. All patients who underwent MPFLr, non-distalizing TTO, trochleoplasty, or a combination of the three operations from 2016-2021 by one of the participating attending surgeons were included. Radiographs obtained pre-operatively, 2 weeks post-operatively, and 3 months post-operatively were analyzed. Caton-Deschamps Index (CDI) and a linear measure from the distal pole of the patella to the proximal, anterior tibial plateau were collected for each patient. Data was deidentified and pooled across the four centers. Patients were excluded if they did not have pre-operative imaging stored in the medical record or if their lateral knee x-ray did not meet study criteria (15-65 degrees of flexion and less than 8 millimeters of overhang of the femoral condyles). 1x2 repeated measures ANOVA for two time points (pre-operative and 2 weeks post-operative) and 1x3 repeated measures ANOVA for three time points (pre-operative, 2 weeks post-operative, and 3 months post-operative) were conducted. p-values less than 0.05 were considered statistically significant. Results: A total of 262 knees met inclusion criteria (Table 1). 117 underwent isolated MPFLr, 106 MPFLr and TTO, and 39 MPFLr and trochleoplasty. CDI was 1.13, 1.11, and 1.09 preoperatively in each group, respectively. CDI decreased by a statistically significant amount 2 weeks post-operatively in all groups. The decrease was -0.08 for isolated MPFLr, -0.10 for MPFLr and TTO, and -0.15 for MPFLr and trochleoplasty (p=0.001 for each). A decrease of over a millimeter was also seen in all groups at 2 weeks when looking at the linear measure from the distal poll of the patella to the proximal, anterior tibial plateau. Exact changes were MPFLr = -1.20 mm (p=0.028), MPFLr and TTO = -1.28 mm (p=0.001), and MPFLr and trochleoplasty = -1.85 mm (p=0.006). At three months, CDI remained decreased in the MPFLr and TTO and MPRLr and trochleoplasty groups with exact decreases of -0.10 and -0.14, respectively (p = 0.001 for both). The linear measure also remained decreased at three months, with changes of -2.59 mm for MPFLr and TTO and -2.29 mm for MPFLr and trochleoplasty (p = 0.001 for both). The isolated MPFLr group failed to reach statistical significance for either CDI or the linear measure at three months. Conclusions: Our results demonstrate that patellar instability surgery affects patellar height, even when a distalizing tibial tubercle osteotomy or patellar tendon shortening are not performed. A decrease was seen in patellar height 2 weeks post operatively, whether the patient underwent MPFLr, MPFLr and TTO, or MPFLr and trochleoplasty. This was also observed at 3 months in the linear measure of MPFLr and TTO group and the CDI of the MPFLr and trochleoplasty group. All other groups did not reach statistical significance at 3 months. These results have important clinical implications. They suggest that these patellar instability surgeries decrease patellar height. Surgeons can expect a decrease in CDI of approximately 0.1 and a shortening of 1-2 mm in the distance between the distal patella and the proximal plateau when performing these procedures. This means patients with borderline patellar alta may have their alta satisfactorily treated without a distalizing TTO. However, if a CDI change of more than 0.1 is needed, distalizing osteotomy or patellar tendon shortening may be indicated.